Inventing Hebrews: design and purpose in ancient rhetoric - Martin, Michael W. (Society for New Testament Studies Monograph Series, 2018)
Inventing Hebrews uncovers a template of arrangement ubiquitous in antiquity as the key to the conundrum of Hebrews' structure and purpose